Developing and Growing the Church Through Missionary Work: A Case of Methodist Church in Kenya - Kinoti, Mary; Nteere, Nicholas Mutwiri (International Journal of Professional Practice, 2021)
Developing and growing the church requires great commitment, zeal, and passion. This obligation requires a group of individuals determined to promote a local incarnation of the body of Christ through themselves. In order to develop and grow the church, misionaries need to espouse the discernment of spiritual endowments of the congregation, and inspire them to use these gifts in planting of churches. This initiative affirms the centrality of missionary work in developing and growing the church. The Methodist Church started planting Churches in Kenya 150 years ago. Eventually, the Methodist Church in Kenya (MCK) became autonomous. Since then, the Church has grown in different parts of the country. This growth is attributable to the motivation of missionary work that has led to the planting of churches in rural and urban areas. Missionary work during the days of early Christianity was very effective in establishing the basis for the present Christian practice. However, over time, the church seems to have abandoned missionary work in their quest to develop and grow the church. Nonetheless, the Methodist Church in Kenya has used different strategies to grow the church. These strategies need to be evaluated in line with biblical foundations and relevant literature. Thus, this article explores the use of missionary work in developing and growing the church. The article adopted a qualitative approach. Data was collected from secondary sources, and analyzed through themes and patterns. The findings indicate that missionary work is the sine qua non or integral part for church growth. The study recommends that the church sustains missionary work, since through the missionary work, communities and the entire world will be changed for God